Type of Dominant Personality in Coronary Artery Heart Disease Patients - Beny Prastyo; Abdurrachman Abdurrachman; Yunias Setiawati; Rerdin Julario; Lukman Hakim Andira (Humanistic Network for Science and Technology (HNST), 2019)
Coronary heart disease is one of the leading causes of death in Indonesia. Personality is one of the risk factors of coronary heart disease. The aim of the study was to investigate the dominant personality according to Big Five Personality in patients with coronary heart disease. We used an analytical descriptive study with cross-sectional design. The samples taken were patients with coronary heart disease in Dr. Soetomo General Hospital Surabaya in May 2019. Data of personality were collected using the Big Five Personality questionnaire. The result showed that the dominant personality according to Big Five Personality in patients with coronary heart disease was conscientiousness. Keywords: big five personality; coronary heart disease; personality type